Students’ Perception on Flipped Classroom Approach in Learning Communicative English among Community College Students - Fathilah Begum Mohamed Maidin; Siti Shuhaida Shukor (The English Teacher, 2021)
Learning English as a second language has never been straightforward, especially when it requires the learners to speak in the target language during the lesson. Students have the tendency to keep quiet and refuse to communicate in English due to many factors. In encouraging students to speak in the target language during the class, many English language instructors have pursued new and interesting approaches. One of the approaches includes flipped classrooms. Flipped classroom allows students to learn the concepts of one particular topic at their own time and pace whilst spending the classroom session on hand-on activities. This study investigates students’ perceptions of using flipped classroom approaches in their Communicative English classroom. The aim of this study was to determine whether a learning approach such as flipped classroom had any influence over students’ attitudes and motivation. The participants of this study were 106 students at Taiping Community College. This study employed a quantitative research design via survey. Before gathering the students’ opinion, the participants had experienced the flipped classroom approach during the Communicative English lesson. After that, a set of questionnaires were distributed to the participants and data were analyzed descriptively. Results revealed that most students had positive perceptions towards the use of flipped classrooms and were highly motivated to learn and had positive attitudes towards the implementation of the flipped classroom approach. This study provides insights for Malaysian community college lecturers to adopt flipped classroom approach in their teaching, especially in the Communicative English lesson.